Association Between Tinnitus and Hypertension: A Cross-Sectional Analysis of the National Health and Nutrition Examination Survey. Issue 7 (4th August 2022) - Patel, Shrey D.; Patel, Shiv; Finberg, Ariel; Shah, Viraj N.; Mittal, Rahul; Eshraghi, Adrien A.
Abstract : Objective: Evaluating the association between arterial hypertension and tinnitus while controlling for gender, race, diabetes, hearing loss, and depression as potential confounders. Study Design: The present study employed a cross-sectional design. Setting: Health interviews were conducted in the respondents' homes. Patients: Respondents represent a nationwide sample of the noninstitutionalized civilian population of the United States. A total of 5, 735 adults were identified by the NHANES 2015 to 2016 questionnaires. Interventions: Questionnaires were administered to each participant. Main Outcome Measures: Participants' responses regarding tinnitus, hypertension, hearing loss, depression, diabetes, and demographics were used to evaluate potential associations. Multivariate logistic regression analyses were conducted on different age groups with the presence of hypertension as the response variable. Results: Participants aged 20 to 39 with tinnitus were significantly more likely to be diagnosed with hypertension (OR = 2.49; p = 0.024) after adjusting for potential confounding. No significant association between tinnitus and hypertension was found for older age groups. The diagnosis of diabetes was associated with hypertension in ages 20 to 39 (OR = 7.11; p = 0.001), 40 to 59 (OR = 3.45; p = 0.020), and 60 to 69 (OR = 3.89; p = 0.032). Conclusions: Tinnitus is associated with hypertension in younger age groups of 20 to 39 years of age but not in age groups greater than 40 years. Diabetes is also associated with hypertension in individuals aged 20 to 69 years. This finding of tinnitus as a risk factor for hypertension in younger populations may inform better clinical practice and lead to earlier detection of hypertension in at-risk patients.